Community-Based Exercise for Upper Limb Paresis: A Controlled Trial With Telerehabilitation. (September 2014) - Benvenuti, Francesco; Stuart, Mary; Cappena, Veruska; Gabella, Sara; Corsi, Sara; Taviani, Antonio; Albino, Antonio; Scattareggia Marchese, Sandro; Weinrich, Michael
Background . Arm paresis remains a major impairment after stroke despite the best conventional rehabilitation. Randomized, controlled trials of intensive exercise programs have demonstrated improvements in arm function for patients with chronic stroke. However, the gains achieved have been relatively modest for the large investments in patient and therapist time. Objective . To evaluate the safety, acceptance, adherence, and effectiveness of a community-based exercise program for upper limb paresis in patients with chronic stroke and the effects of telerehabilitation monitoring in kiosks distributed through the community. Methods . Longitudinal cohort with geographic control group. The experimental group received devices needed for a home exercise program based on the Carr and Shepherd "Motor Learning Program" and were instructed to practice the exercises at least twice a week at the kiosk and at least 3 more days a week at home. The control group received usual care. Results . Compared with the control group, patients in the experimental group demonstrated significant gains in arm function as measured by the Wolf Motor Function Test, 9-Hole Peg Test, Motricity Index, and Nottingham Extended Activities of Daily Living Questionnaire. The intervention received high satisfaction ratings and produced no adverse events. Only 30% of the subjects attended kiosks regularly. Outcomes for this group did not differ significantly from those who only practiced at home. Conclusions . Home- and community-based exercise for arm paresis is safe and effective. Telerehabilitation interventions will need additional enhancements to improve effectiveness. The optimal upper extremity exercise prescription poststroke remains to be established.